'Sitting on a wobbly chair': mental health and wellbeing among newcomer pupils in Northern Irish schools. Issue 2 (2nd April 2020) - McMullen, John; Jones, Sharon; Campbell, Rachel; McLaughlin, Judith; McDade, Barbara; O'Lynn, Patricia; Glen, Catherine
ABSTRACT: Schools in Northern Ireland (NI) have become increasingly diverse with the numbers of newly arrived migrant pupils more than doubling over the past decade. While studies have shown an increasingly high prevalence of mental health difficulties among young people in NI generally, there is a paucity of research with at risk groups, including members of ethnic minority communities. This paper draws on data from a study commissioned by The Education Authority (NI) that investigated the mental health needs of newcomer pupils in schools in NI according to newcomer pupils themselves, as well as school staff and youth workers who support them, and to make recommendations for future development. Participant views and lived experiences were explored through questionnaires, online surveys, semi-structured interviews, and focus group discussions. Results suggest that, while many newcomer pupils have adapted well and display average levels of emotional well-being, many have experienced a range of adversities that may negatively impact mental health. Recommendations are made that relate to the emergent themes: to consider pre-existing stress and trauma (especially among refugees); respect socio-cultural differences and perspectives; foster relationships and collaboration; and empower and support schools.